Keterkaitan antara pandemi covid-19 dengan eksploitasi alam - Priyaji Agung Pambudi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
Exploitation does not completely environmentally principles, ecosystems store biodiversity, including dangerous zoonotic viruses. The emergence of the Covid-19 pandemic is believed to be zoonotic that spreads infecting a hundred million people. This study was conducted to analyse the relationship between pandemic and exploitation, using a literature review of articles, documents, reports, papers, WHO information, and the Indonesian Covid-19 Task Force. There is a proven connection between the Covid-19 pandemic and the exploitation of nature. It narrows or even eliminates habitats and suppresses their lives, organisms respond by the expansion that is often closer to humans. Exploitation facilitates organisms as natural or intermediate hosts that have the potential zoonosis. Homologous analysis result of SARS-CoV-2 had a complete genome similarity of 93.7%, ORF1ab 96.5%, N protein 96.9%, and spike protein 92.86% with bat-coronavirus (Rhinolophus affinis Horsfield, 1823). This species, spread in South and Southeast Asia, to be a traditional medicine for respiratory. Wildlife animals as medicine should be limited, especially protected animals because trade with risky for zoonoses and potential of epidemics and pandemics. It can be overcome if ecosystem stability and provide proportional living space for other organisms, so that harmonious and sustainable interactions come true.